Translation, conversion and the containment of proliferation - Israel, Hephzibah (Religion, 2019)
This article examines the role of translation in conversion to Christianity in South Asia to argue that recognizing translation as a culturally constructed and contingent category entails investigating different definitions of translation at work within different religious cultures. This helps challenge the assumption that a focus on translation is primarily a consideration of equivalence. Rather than take equivalence as universal or normative in examining the role of translation in religious conversion, this article draws attention to alternative definitions and metaphors of translation that are not concerned chiefly with equivalence which complicate the construction of categories such as religion and conversion in the South Asian colonial context. If translation serves as a regime of interpretation by which religious converts construe their relationship with past and present religions, this article argues it is important to engage with their diverse characterizations of translation.